2024
DOI: 10.1002/erv.3088
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories and predictive factors of weight recovery in patients with anorexia nervosa completing treatment. A latent class mixed model approach

Laura Di Lodovico,
Amir Al Tabchi,
Julia Clarke
et al.

Abstract: BackgroundTreatment of anorexia nervosa (AN) sometimes requires hospitalisation, which is often lengthy, with little ability to predict individual trajectory. Depicting specific profiles of treatment response and their clinical predictors could be beneficial to tailor inpatient management. The aim of this research was to identify clusters of weight recovery during inpatient treatment, and their clinical predictors.MethodsA sample of 181 inpatients who completed a treatment programme for AN was included in a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…For example, a recently published study has found that a higher BMI was associated with more severe ED psychopathology, more depressive symptoms, anxiety sensitivity, experiential avoidance, and lower mindfulness in patients across the whole spectrum of restrictive, binge-purge, and atypical AN [13]. Furthermore, recent research indicates that body weight at the start of inpatient treatment as well as weight gain kinetics during inpatient therapy for AN might help to predict treatment outcomes, improve clinical decision-making, and manage expectations of patients and clinicians [14]. Thus, a collaborative and more accurate way of measuring body weight might improve the clinical formulation and the decision-making process and lead to better treatment success and a more pleasant treatment experience in people with AN.…”
Section: Author Detailsmentioning
confidence: 99%
“…For example, a recently published study has found that a higher BMI was associated with more severe ED psychopathology, more depressive symptoms, anxiety sensitivity, experiential avoidance, and lower mindfulness in patients across the whole spectrum of restrictive, binge-purge, and atypical AN [13]. Furthermore, recent research indicates that body weight at the start of inpatient treatment as well as weight gain kinetics during inpatient therapy for AN might help to predict treatment outcomes, improve clinical decision-making, and manage expectations of patients and clinicians [14]. Thus, a collaborative and more accurate way of measuring body weight might improve the clinical formulation and the decision-making process and lead to better treatment success and a more pleasant treatment experience in people with AN.…”
Section: Author Detailsmentioning
confidence: 99%